El conservadurismo evangélico en el Perú: identidades y proceso de hegemonización (1980-2020) - Fonseca, Juan (2022)
One of the issues gaining attention in the Peruvian social sciences is the growing political power harnessed by Evangelicals, especially on its ultra-conservative wing. This article will examine the factors that led to the progressive hegemonization of fundamentalism within the Peruvian Protestantism from 1980 onwards. This means, firstly, to review the key concepts of the discussion about the Evangelical identity, as well as to analyze the internal ideological tensions within said religious community. Thereby, delineating the historical process that has taken fundamentalism from a minority religious and cultural force into a political force aspiring to hegemonize the Peruvian religious and political stage.